Electromyographic activity of the lower limb muscles during salat and specific exercises - Mohd Khairuddin, Mohd Safee; Wan Abu Bakar, Wan Abas; Fatimah, Ibrahim; Noor Azuan, Abu Osman (2012)
. [Purpose] This study investigated the activity of the rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA) and gastrocnemius (Gas) muscles of healthy subjects during salat and specific exercises using surface electromyography (EMG). [Methods] A group of undergraduates aged between 19 to 25 years voluntarily participated in this study. For the assessment of the RF muscle, the subjects were asked to perform salat movement [standing to prostration (STP)] and squat exercise (SE) and for the BF, TA and Gas muscles, subjects were asked to perform salat (bowing) and the toe touching exercise (TTE). The electromyograms of the muscles were recorded and analyzed. [Result] The findings indicate that there were contractions of the muscles during the salat and exercises with difference EMG levels. Wilcoxon’s Rank Sum Test found a statistically no significant differences between salat and the specific exercises for RF, BF and Gas. For TA, the test revealed a statistically significant difference between salat and the specific exercise with a difference of 5.67%MVC. [Conclusion] Salat may be useful in warm up or in rehabilitation programs. This pilot study conducted initial research into the biomechanical responses of human muscles in various positions of salat